SES (Social and Emotional Skills)-based Plastic Waste Recycling Activities as a Means of Strengthening the Values of the Pancasila and Rahmatan Lil Alamin Student Profile Strengthening Project (P5PPRA) - Geta Rohmawati; Elya Umi Hanik (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
P5RA is a co-curricular activity in the Merdeka Curriculum. Researchers identified the problem of high volumes of plastic waste in the madrasah environment, so the P5RA project, with a recycling theme, was implemented to strengthen the Social Emotional Skills (SES) sub-domain for students. This study aims to describe the implementation and impact of SES-based P5RA recycling on Phase C students. The study used a qualitative, field-research approach and was carried out at MI NU Miftahul Ulum Loram Kulon Kudus. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and concluding. The results of the study show that: (1) The implementation of SES-based P5RA plastic waste recycling takes place through the stages of planning, implementation, evaluation, and follow-up. (2) This program has a significant impact on instilling the values ​​of Pancasila Students and rahmatan lil’ alamin in Phase C students, especially the values ​​of cooperation, creativity, dynamism, and innovation (tathawur wa ibtikar). Furthermore, the three sub-domains of SES responsibility, emotional control, and cooperation were successfully internalized. Overall, this research has positive implications for strengthening character education, environmental awareness, and developing the creative economy, while also contributing to sustainable plastic waste management within the madrasah environment and surrounding communities.